2006
DOI: 10.1021/jf061087w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extraction Solvent Mixtures on Antioxidant Activity Evaluation and Their Extraction Capacity and Selectivity for Free Phenolic Compounds in Barley (HordeumvulgareL.)

Abstract: Four kinds of solvent extracts from three Chinese barley varieties (Ken-3, KA4B, and Gan-3) were used to examine the effects of extraction solvent mixtures on antioxidant activity evaluation and their extraction capacity and selectivity for free phenolic compounds in barley through free radical scavenging activity, reducing power and metal chelating activity, and individual and total phenolic contents. Results showed that extraction solvent mixtures had significant impacts on antioxidant activity estimation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
179
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(230 citation statements)
references
References 36 publications
31
179
1
5
Order By: Relevance
“…Our results indicate that aqueous extracts had the best impact on these antioxidant activities. These findings are partially in agreement with those of Zhao et al (2006), who found water as an efficient solvent for reducing power evaluation. These observations suggested that solvent polarity and nature of the plant phenols greatly influence the antioxidant extraction.…”
Section: Reducing Powersupporting
confidence: 92%
“…Our results indicate that aqueous extracts had the best impact on these antioxidant activities. These findings are partially in agreement with those of Zhao et al (2006), who found water as an efficient solvent for reducing power evaluation. These observations suggested that solvent polarity and nature of the plant phenols greatly influence the antioxidant extraction.…”
Section: Reducing Powersupporting
confidence: 92%
“…Additional analytical data of barley and malt analysis (Žabčice). as for malt (n = 60, r ranged from 0.624 to 0.867, p < 0.01), which is in agreement with the data already published 11,29 . Additional analytical data of selected barley and malt samples are summarized in Table IV.…”
Section: Relationship Between Antioxidant Activity and Individual Andsupporting
confidence: 92%
“…Several types of polyphenol extraction have been described 6,7,11,19,22,23,26,29 . The mixture of water with organic solvent is one of the most used.…”
Section: Introductionmentioning
confidence: 99%
“…• ) Assessment of the ability to scavenge free radicals in relation to the superoxide radical is based on the generation of radical O 2 -• throughout the system by enzymatic reaction, catalyzed by the enzyme hypoxanthine xanthine oxidase (Zhao et al 2006). A sample (100 µL) was added to the reaction solution containing 100 µL of 30 mM disodium ethylenediaminetetraacetic acid (EDTA), 100 µL of 3 mM hypoxanthine (HPX), and 200 µL of 1.42 mM nitrotetrazolium blue chloride (NBT).…”
Section: Superoxide Anion Radical Methods (O 2¯mentioning
confidence: 99%
“…• ) The antiradical activity studies of samples and analytical standards with the hydroxyl radical at different concentrations were performed using the 2-deoxy-D-ribose method proposed by Zhao et al (2006) with some modifications. The FeCl 3 • 6H 2 O and ascorbic acid were prepared in milli-Q water before use.…”
Section: Hydroxyl Radical Methods (Homentioning
confidence: 99%